The Role of Teachers In Transferring Educational Values From Surah Yasin Verses 77-83 : Challenges, Strategies and Learning Implications - Umroh, Hayail; Gade, Syahbudin (PGMI IAIN Lhokseumawe, 2025)
This study aims to analyze the role of teachers in transferring the values of the Qur'an, particularly Surah Yasin verses 77-83, in shaping students' Islamic character based on monotheism (tauhid), faith in Allah as the Creator, and belief in the Day of Resurrection. This research uses a qualitative method with a library research approach. The findings indicate that Surah Yasin verses 77-83 contain relevant educational values, such as strengthening faith (tauhid), awareness of Allah's signs of power, belief in the Day of Resurrection, and the importance of moral and spiritual responsibility. Teachers play a strategic role in integrating these values into learning through methods such as tadabbur, group discussions, contextual approaches, and project-based learning. However, the main challenge lies in the limited ability of teachers to deeply analyze Qur'anic interpretation. In conclusion, Qur'anic interpretation training is essential to improve teachers' competence in effectively conveying the values of Surah Yasin verses 77-83. By implementing these values, students can develop a strong Islamic character, adopt a productive attitude, and view every action as an act of worship. This study recommends developing teachers' competencies through holistic training to create meaningful, relevant, and Qur'an-based learning.